Penguatan Kolaborasi Sekolah dan Masyarakat melalui Seminar Ilmiah untuk Meningkatkan Kualitas Pendidikan Dasar - Rusmin Husain; Irvin Novita Arifin; Idan I. Pakaya (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Collaboration between schools and communities plays an important role in supporting the improvement of the quality of basic education. However, community involvement in education is still largely limited to administrative activities and has not fully developed into participatory collaboration in supporting learning processes and school development. This community service activity aimed to strengthen collaboration between schools and communities through a participatory scientific seminar in supporting inclusive and sustainable basic education. The activity was conducted on April 30, 2026, in Gorontalo involving 32 participants consisting of lecturers, postgraduate students, principals, teachers, and education communities. The activity was implemented through seminar sessions, interactive discussions, reflective dialogue, and collaborative problem-solving related to educational issues. Evaluation was conducted using participant observation, reflection sheets, and participant response questionnaires. The results showed that 87% of participants actively participated in discussions, 84% experienced increased understanding regarding school–community collaboration, and 90% gave positive responses to the participatory seminar model. In addition, the activity generated several strategic recommendations related to participatory learning, parental involvement, collaborative school governance, and the optimization of school facilities as educational and social centers. Therefore, participatory scientific seminars can serve as an effective community service model in strengthening collaborative educational ecosystems in basic education.